Can Different Teaching Practices Influence the Connection between Social Status and Student Achievement? - Dragana Gundogan; Dušica Malinić; Mladen Radulović (University of Belgrade, Teacher Education Faculty, 2020)
Starting from the fact that there is no consensus on the way in which school factors mediate the influence of social status on achievement, we wanted to examine how teaching practices affect the relationship between social status and student achievement. More precisely, we tried to determine whether the intensity of the correlation between social status and student achievement on the TIMSS test differs among students whose teachers use different ways of teaching (practices that are more in line with transmissive teaching or practices more in line with engaging teaching). To answer this question, we used the data collected within the TIMSS 2015 research conducted in Serbia, which included 160 schools, 192 primary school teachers, and 4036 students. The collected data were analyzed using factor analysis of variance and correlation analysis. The results showed that (1) there is a moderate positive correlation between social status and student achievement, (2) that there is no correlation between teaching practices and student achievement, and that (3) teaching methods mediate the relationship between social status and achievement. The mediating role of teaching approaches is reflected in the fact that the stronger intensity of the correlation between social status and achievement is, the teaching itself tends to be more transmissive and less engaging. The obtained findings suggest that teaching approaches in the classroom can alleviate social inequality, and that their concept has to be as much as possible in accordance with the principles of engaging teaching.